Effects of Dietary Mineral Premix Reduction or Withdrawal on Broilers Performance - Sayadi, A. Jafari; Navidshad, B.; Abolghasemi, A.; Royan, M.; Seighalani, R. (International Journal of Poultry Science, 2005)
This experiment was conducted to evaluate the effects of withdrawing or reduction mineral premix from diets at 21 to 42 days of age on broiler performance. Two hundred and eighty day old broiler chickens of Cobb 500 strain used in a completely randomized design with 7 treatments, 4 replicates each. Chickens were fed on a common starter diet with suggested mineral premix level (0.5%) for first three weeks age. Seven corn-soybean meal based grower diets with different mineral premix levels were used at 4 to 6 weeks of age. The dietary treatments were the following: T1) 0.5% mineral premix at weeks 4, 5 and 6 T2) 0.5% mineral premix during weeks 4 and 5, and 0.25% at week 6 T3) 0.5% mineral premix during week 4 and 0.25% during weeks 5 and 6 T4) 0.25% mineral premix at weeks 4, 5 and 6 T5) 0.5% mineral premix at weeks 4 and 5 and omitting it during week 6 T6) 0.5% mineral premix during week 4 and removing it during weeks 5 and 6 T7) using diet without mineral premix during weeks 4, 5 and 6. Feed intake and weight gain were measured at the end of each week and feed conversion ratio was calculated. Results showed that reduction or withdrawal of mineral premix from diets in different weeks of grower period, didn`t affect feed intake. In weeks 4 and 5, there was no significant difference in weight gain and feed conversion ratio, but in week 6, weight gain of treatment T1 which fed diet with 0.5% mineral premix at whole the experiment period was significantly higher and its feed conversion ratio was significantly lower than other treatments. The overall results of the present study indicated that it`s possible to reduce or remove dietary mineral premix during at least first 2 weeks of grower period but longer withdrawal can negatively affect weight gain and feed conversion of broiler chickens. This decline in dietary mineral premix maybe causes an increase in cost per kg of produced chickens.